Instrumental Analysis of Siddha Antidote Surai Karuppu - Yogeswari, Chandrabose; Rajendran, Vijayalakshmi; Kannan, Ariharikrishnan; Balasubramani, Abarna; Ponnappan, Shanmugapriya; Ramachandran, Madhavan (Asian Journal of Biological and Life Sciences)
Background: Lagenaria siceraria (Mol.) Standl., commonly known as bottle gourd, is a medicinal plant from the Cucurbitaceae family with established therapeutic potential. In Siddha medicine, purified Lagenaria siceraria rind is traditionally used as an antidote for mercury poisoning, particularly targeting renal manifestations. Surai Karuppu, prepared by charring the dry shell of bottle gourd into activated charcoal, is believed to act on renal cells and exhibit therapeutic efficacy in treating chronic kidney disease and uremic toxins. Objectives: This study aimed to assess the functional groups and particle characteristics of Surai Karuppu using instrumental analysis to provide scientific evidence supporting its traditional therapeutic claims. Materials and Methods: Surai Karuppu was prepared by burning dry bottle gourd shell to activated charcoal. Fourier Transform Infrared (FT-IR) spectroscopy was performed using a BRUKER Optik GmbH TENSOR 27 spectrometer in the range of 4000-400 cm⁻¹. Scanning Electron Microscopy (SEM) analysis was conducted using CARL ZEISS microscope at 20k magnification to evaluate morphological characteristics and particle size. Results: FT-IR analysis revealed characteristic absorption bands at 3428 cm⁻¹ (O-H stretching), 2929 cm⁻¹ (C-H stretching), 1744 cm⁻¹ (C=O stretching), and bands at 1618, 1370, and 1047 cm⁻¹ indicating presence of phenolic compounds, alkanes, carbonyl groups, alcohols, and ethers. SEM images showed well-aggregated nanoflakes-like morphology with smooth surface and average particle size ranging 4-5.5 μm. Conclusion: Instrumental analysis confirmed the presence of functional groups crucial for therapeutic activity, supporting the traditional use of Surai Karuppu as an antidote with potential antioxidant properties.
Keywords: Surai Karuppu; SEM; FTIR; Mercury Antidote.